Enterprise Ontology According to Roman Ingarden’s Theory of Objects - Andreasik, Jan (Regional Barometer. Analyses & Prognoses, 2009)
In the paper, original ontology is defined. This ontology is based on the concept apparatus of theory of object proposed by Roman Ingarden - a Polish philosopher. In Section 2, the author presents a definition of individual object according to this theory. In this definition, the following concepts are included: essence, form, way of existence, constitutive nature, subject of properties, endowment of properties, properties, state of thing, relation. By analogy, the author defines one’s own concepts of the enterprise ontology: enterprise essence, form of competence system, content of assessments, enterprise vision, enterprise competence system, competence assessment, assessment criteria, score trajectories, grammar of trajectories, enterprise condition, competence potential condition, competence gap condition, act of explanation. According to the presented enterprise ontology, there are created descriptions of cases in the intelligent system for recognition of enterprise condition designed on the basis of the CBR (Case-Based Reasoning) methodology.